Nablus Medical Complex - Ahmed Taha; Ahmed Abu Jaradeh; Ziad Amer (My University, 2025)
Nablus Charity Medical Complex, established in 1986 and renovated in 2016, is located in Nablus City and managed by the Nablus Zakat Committee. The complex aims to provide exceptional medical services at affordable prices, targeting all segments of society, especially marginalized groups, orphans, and low-income families. It houses several medical departments, including orthopedics, pediatrics, dentistry, ophthalmology, and emergency care. The current operational system relies on traditional methods that are slow, poorly organized, and lack information integration, leading to frequent errors and appointment overcrowding. Patients can book appointments through phone calls, in-person visits, or social media, but these methods are often inefficient. Our graduation project aims to design a computerized booking and registration system to address the shortcomings of the current system. This includes analyzing data to improve appointment management and incorporating predictive tools to help the complex optimize resources and enhance service quality. The new system focuses on improving appointment scheduling, accelerating data access, reducing errors, and offering greater flexibility for handling patient records. The project also features a modern website with dedicated pages for each role in the complex: • Patients: They can book appointments, view their specific pages. • Doctors: They can manage appointment schedules, access patient data, and input diagnostic reports. • Management: They can oversee systems, monitor statistics, and make data-driven decisions. The new system aims to enhance overall efficiency through accurate appointment scheduling, improved communication between departments, and providing detailed analytics to assist doctors and management in delivering better services.